Peningkatan Efisiensi Rantai Pasok UMKM di Desa Wabula Satu untuk Memperluas Akses Pasar dan Meningkatkan Daya Saing Produk - Dzulfikri Azis Muthalib; Husin Husin; Unika Oktaviani Damau; Harmiaty Bahar; Windayani Windayani; Conny Conny; Juharsah Juharsah; Nursaban Rommy Suleman; Laode Asfahyadin Aliddin; Ambo Masse (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to enhance supply chain efficiency and expand market access for Micro, Small, and Medium Enterprises (MSMEs) in Wabula Satu Village, Buton Regency, Southeast Sulawesi. The main problems faced by MSMEs include inefficient supply chain management, limited production coordination, and low utilization of digital technology for product marketing. The program was implemented using an educational-participatory approach through a series of training sessions, simulations, and mentoring activities. The results revealed significant improvements in participants’ understanding of supply chain management, production efficiency, and digital marketing skills, particularly through social media and marketplace platforms. MSMEs also showed progress in branding and product packaging, while collaborative networks were established to support collective raw material procurement and joint distribution. This program has contributed to improving local business competitiveness, productivity, and sustainability. Moreover, it demonstrates an effective community empowerment model based on technology adoption and collaboration to strengthen village economic resilience in the digital era.